Under slow flow conditions, daily rates of canopy photosynthesis of marine macrophytes were insensitive to model choice and flow‐rate. Issue 4 (22nd July 2015) - Nishihara, Gregory N.; Yamada, Chizuru; Kimura, Ryutaro; Terada, Ryuta
Summary: Water motion drives the flux of suspended and dissolved material (e.g., nutrients, gametes, and dissolved oxygen) to and from macrophyte canopies, and is one of the most important mechanisms that can regulate the growth, survival, and persistence of marine macrophytes populations. At small spatial scales (e.g., lamina or leaves and individuals), increasing flow‐rates have been demonstrated to enhance physiological processes, especially photosynthesis rates, and we expected a similar response at the canopy scale. We conducted seven experiments over 25 days using a pair of open‐air flow‐chambers under natural light, temperature, and seawater conditions. In the four marine macrophyte ( Sargassum piluliferum, S. siliquastrum, S. thunbergii, and Zostera marina ) canopies examined, an increase in flow‐rate did not enhance photosynthesis rates. The odds that daily gross photosynthesis rates increase with a decrease in flow‐rates was 1.77 to 1. We also examined if two non‐linear equations and one linear equation, often used to describe the relationship between photosynthesis to photosynthetic photon flux density (PPFD), biased estimates of the daily rates of photosynthesis and respiration. It was revealed that the functional form of the equation strongly influenced photosynthesis and respiration rate estimates at short time scales (i.e., minutes), however, daily rates were insensitive to the type of equation used to model the relationship between photosynthesis and PPFD. We suggest that the predominance of photosynthesis rates occurring in under‐saturating PPFD conditions (> 40 % of daylight hours) may be one of the reasons for this insensitivity.